Art collaboration as a branding tool for the post-industrial region - Igor M. Alikperov; Aleksey A. Mezyurov (Управление культурой)
Territory branding is a condition and a consequence of the successful positioning of the territory not only at the All-Russian, but also at the international level. The competitive environment in which cities and regions of the country are developing requires not only the preservation of industrial, scientific, cultural heritage, but also the saturation of leisure life with interesting, original cultural events, an effective tool for the implementation of which is art collaboration.The objective of the study is to reveal the possibilities of art collaboration in creating new cultural products that will help make the urban space more creative, competitive, which will allow creating an understandable brand of the region and solving many municipal socio-economic problems. The article discusses the concepts of "territory branding", "art collaboration", "co-branding", provides modern methods for classifying art collaborations, analyzes the Yekaterinburg experience of their creation, and models possible problems of project partnership. Identified and analyzed two formulas for the interaction of partners in the creation of cultural products - “art and art” (for example, the opening of the Egida art gallery in the Sverdlovsk Philharmonic), and “art and business” (joint projects of the telecommunications company Tele-2 and the Yekaterinburg Museum of Fine Arts ). The article uses the results of current scientific research, theoretical research methods: classification, modeling, analysis, synthesis, generalization, observation. The results of the study show that the use of art collaborations at the moment is a promising vector for the development of territories, so the authors plan to continue this study in terms of studying possible organizational forms of partnership, an art collaboration algorithm, which will allow the territory to become a competitive space not only to attract the attention of tourists and entrepreneurs from other regions, but will also strengthen the loyalty and patriotism of the inhabitants of the territory.